Good, Pleasure and Types of Friendships in Aristotle’s Eudemian Ethics (VII 2) - Smolak, Maciej (Peitho. Examina Antiqua, 2016)
In EE H 2 Aristotle presents a typology of friendship starting from the puzzle whether the good or the pleasure is the object of love. But after indicating the reasons for loving and identifying three types of friendships he raises three important questions (1237a19–21): (1) whether there is any friendship without pleasure; (2) how the hedonical friendship differs from the ethically friendship; (3) on which of the two things the loving depends: do we love somebody because he is good, even if he is not pleasant, at any rate not for his pleasantness? The present article attempts to give answers to questions 1–3 and show that despite the coincidence of good and pleasure and the important role of pleasure in the hedonical and ethical friendship the typology does not lose its validity.